Legalitas Usaha Sebagai Strategi Awal Pengembangan UMKM Di Kelurahan Klampok Kota Blitar - Setyo Budiwitjaksono, Gideon; Maghfirotika, Azaaima; Azza Syifana, Ananda; Yafi Maulana, Bintang; Rizky Wijayanti, Annisa; Saniyyah (BERBAKTI : Jurnal Pengabdian Kepada Masyarakat, 2023)
There are still many MSMEs in Klampok Village, Blitar City that do not have business legality. These business actors underestimate the legality of business on the grounds that without having business legality, the business they run is fine and they still have buyers. According to them, business legality has no effect on sales. Because most MSMEs in the Klampok Village do not understand the existence of a Business Identification Number (NIB) for business legality. Case study and hands-on practice are the methods used in the community service activities this time which were carried out at the NIB Command Post for assistance in making MSME NIB. The results of this NIB mentoring activity were able to improve the abilities and skills of Klampok Village residents, especially business actors regarding the importance of NIB in increasing economic resilience and faster and safer business development in terms of business legality. carried out in the Klampok Village Hall has gone according to plan, namely the awareness of MSME actors regarding business legality ownership which will have a positive impact on their business in the future.